OWNERSHIP TYPE AND COMPANY PERFORMANCE: EMPIRICAL STUDIES IN THE INDONESIAN STOCK EXCHANGE - Fransiska Soejono (Faculty of Economics and Business, Universitas Gadjah Mada, 2010)
This study is aimed to test the difference in performance among companies with various types of ownership (foreign, state, and private) on a sample of 206 companieslisted in ISE (Indonesian Stock Exchange) between 1999-2006 resulting in 795 company year observations. The ANCOVA model and multiple comparison methods are used to test the hypothesis that private-owned companies have better performance than state-owned enterprises and foreign-owned companies have better performance than private-owned companies. Contrary with the hypothesis, the result shows that state-owned enterprises have better performance than private-owned companies. The possible explanation for this is because state-owned enterprises have more experience than private-owned companies (based on LogAge). State-owned firms may get some special facilities (including the easiness to get debt funding) from government. The result also shows that foreign-owned companies have better performance than private-owned companies which support the hypothesis. Foreign-owned companies have more experience in managing enterprises than private-owned companies. Furthermore, foreign-owned companies in some industries tend to be more active in doing investment than private-owned companies. There are some implications of these results. First, different ownership type gives different effect to thecompany’s performance. Second, government can consider foreign ownership in its privatization policy.Keywords: Ownership type, Performance, Experience, Investment.